Children's mental health research the power of partnerships - Hoagwood, Kimberly (New York ; Oxford : Oxford University Press, 2009)
Research in children's mental health lags behind research for adults in part because it is intrinsically context-bound. Making research findings useful & ensuring that they are applied to improve the lives of children & families requires a process of collaboration with many partners, such as teachers, nurses & healthcare providers.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Child mental health -- Research; Child psychology -- Methodology